«Yo todo lo incendio», indifference and indignation on the femicide of María Belén Bernal - Mancero Acosta, Mónica (2023)
Ecuadorian lawyer María Belén Bernal Otavalo was murdered at the National Police School in Quito on September 11, 2002, allegedly at the hands of her husband, a member of the police. This femicide has convulsed Ecuador, even though every 28 hours a woman dies of gender violence. This article presents an analysis of this case from a feminist perspective combined with the so-called affective turn. My argument is that in this process the tears that we live as a society come to the fore, I have noticed that this femicide has been invested with indignation and exposure an “intimate public sphere” by their mother and feminist groups, in an attempt to raise awareness in society and in the search for the assumption of political responsibility by state agents and institutions; while on the government side a manifest indifference has prevailed with a view to minimizing and excluding the feminist agenda from the publica political arena.